DINAMIKA PERKEMBANGAN HUKUM ISLAM - Dr. Andi Herawati, M.Ag (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
Muslims believe that the teachings contained in Islamic law contain the rules that can lead adherents to obtain peace and happiness of the world and the hereafter. On the other hand there is concern and fear that Muslims consistently practice their religion. This makes the kings, scholars and experts of Islamic law looking for loopholes between those who want to implement the teachings of Islam with those who oppose it, so that the various theories that are used in enforcing Islamic law in Indonesia, such as: Theory Kredo (Syahadat); Theory Receptio in Complexu; Theory Receptie; Theory Reseptie Exit; Theory Receptio a Contrario; Theory Recoin (Receptio Contextual Interpretatio); dan Theory Eksistensi.